IDENTIFICATION OF AZOSPIRILLUM SPECIES FROM WHEAT RHIZOSPHERE - L. Rasool; a; M. Asghar; b; A. Jamil; c; S. U. Rehman (Journal of Animal and Plant Sciences, 2015)
Bacteria play an important role in maintaining the health status of soil ecosystem by preforming many biological processes. Among PGPR, Azospirillum is considered as an important genus which is closely-associated with plants and shows potential to degrade organic contaminants, improve the plant health and increase crops yield. The present study was carried out for the isolation of Azospirillum spp, which can be used as crop inoculants. Four bacterial strains were isolated from wheat rhizosphere. The isolates were characterized on the basis of colony, cell morphology, shape, size and motility. Azospirillum strain Azo LR3 has cream/ pink colony color and plump rod, 3µm in size, with typical helical motility. This isolate showed ability to produce indole-3-acetic acid (11.5 µg/ml of culture medium) and gibberellic acid (12.8 µg/ml of culture medium). 16S rRNA genes sequence analysis revealed that isolate belongs to the genus Azospirillum with 96% similarity and phylogenetic tree represent that it was different from the remaining other member of the genus Azospirillum.
Keywords: Azospirillum; rhizosphere; IAA; GA; 16SrRNA